Dose response of yellow and white popcorn hybrids to glyphosate, a premix of 2, 4‐D choline and glyphosate, or dicamba. (30th May 2020) - Barnes, Ethann R; Lawrence, Nevin C; Knezevic, Stevan Z; Irmak, Suat; Rodriguez, Oscar; Jhala, Amit J
Abstract: Popcorn ( Zea mays L. var. everta) is difficult to distinguish from field corn ( Zea mays L. var. indentata) and is produced adjacent or in close proximity to field corn and soybean [ Glycine max (L.) Merr.]. This creates a potential for misapplication or drift of herbicides used in nearby corn and soybean. Field experiments were conducted near Clay Center, Nebraska in 2017 and 2018 to determine the effect of glyphosate, 2, 4‐D choline/glyphosate (premix), or dicamba on the growth and yield of popcorn. Treatments included nontreated control and four rates of glyphosate, 2, 4‐D choline/glyphosate, or dicamba applied post‐emergence (POST) at five‐ or eight‐leaf (V5 and V8, respectively) popcorn growth stages to white and yellow popcorn hybrids. A three‐parameter log‐logistic model was fitted to treatment combination with varying herbicide rates. Glyphosate and 2, 4‐D choline/glyphosate applied at V5 had greater injury, biomass reduction, height reduction, and yield loss than at V8. The two hybrids responded similarly to herbicides at most measurements. At the V8 application, 2, 4‐D choline/glyphosate resulted in greater injury in the white hybrid; however, no hybrid differences in glyphosate sensitivity were observed at the V8 growth stage. Glyphosate and 2, 4‐D choline/glyphosate at 0.25× rates resulted in complete plant death in both hybrids, whereas the highest dicamba dose (2×) caused 11% injury and no biomass reduction, plant height reduction, or yield loss. These results demonstrate the sensitivity of popcorn to glyphosate, 2, 4‐D choline/glyphosate, or dicamba and can be of immediate educational use and practical implementation for popcorn producers, herbicide applicators, and agronomists.